(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article deals with issues related to the competitiveness of regions in the context of macroeconomic instability. The main factors that determine the competitiveness of the subjects of the Russian Federation are analyzed, and the characteristics of the main group of factors that characterize the competitiveness of the regions are presented, and their typification is carried out.